Consumer Protection in Ecommerce: A case Study of Egypt - Habib, Heba (AUC Knowledge Fountain, 2021)
This paper examines electronic contract regulation in the context of business-to-consumer transactions. The technological advancement and cross-border nature of e-commerce have posed significant challenges to the Egyptian legal framework highlighting the limitations of general commercial contract rules with regards to electronic contracts. This thesis argues that access to the courts is hindered by restrictive terms in the electronic contracts over which the Egyptian law has no jurisdictional power. Accordingly, private institutions set the rules in the e-contracts and enforce them through private methods leaving no room for state intervention to ensure the protection of consumers. Hence, the application of national consumer law is impaired by the private practices that shape the transaction to their best business ends. Consumer protection is essential to promote access to the online market since it serves as a safety valve in face of the electronic risks. So, to increase the level of protection for consumers conducting e-transactions, the Egyptian legislator should adopt reforms to control the private mechanism to ensure consumer rights’ application instead of informal negotiations to satisfy consumer’s problems.